Anemia ferropenica y su influencia en el estado nutricional en niños de 1 a 10 años que asisten al hospital Jaime Roldos. Cantón Ventanas Provincia Los Ríos. Septiembre 2017 febrero 2018 - Viteri Campelo, Ruth Mercedes (2018)
Ferropenic Anemia and its Influence on the Nutritional State of childhood has caused many problems in the nutritional status, these problems are unimaginable, correspond to malnutrition and anemia, these pathologies have as a determining factor the nutritional deficiency of the basic nutrients, This is preceded by social, economic and cultural factors, which will be typical of extremely poor societies, which will later prevent adequate and developed growth in children and thus the delay of the people. The pathologies related to poor diet are increasingly frequent and occur in very young populations such as: obesity, diabetes, overweight, malnutrition, deficiency of vitamins and minerals, coronary heart disease, dental caries, and much more. Each of these diseases has nutritional dietary factors. The implications of the coexistence of various nutritional conditions in children present a serious public health problem, in addition to representing high costs in medical care. The investigation of iron deficiency anemia is high incidence of iron deficiency anemia (ferropenic) in children is similar in third world countries. In Ecuador, it reaches 70% of children between six and twelve months, 45% of children between 12 and 24 months and 60% of pregnant women. Hernández indicates that one of the causes of iron deficiency is parasitosis at school age. "There are some parasites that lacerate the gastric mucosa and cause continuous blood loss." In addition, the worldwide prevalence of anemia is 25.4% in school-age children, 12.7% in boys and 23.9% in the elderly. (1) In Ecuador there are few studies on the situation of anemia in children. The prevalence of anemia was determined and the risk factors associated with it were established in children from 1 month to 10 years, who attend the Jaime Roldós hospital. Canton windows province rivers. September 2017 February 2018; the data and laboratory values of the medical records were collected, for the diagnosis of anemia, hemoglobin figures according to age were taken into account, adjusted to the corresponding height.